Predisposing factors on social sciences students career path development in the university: a case study of final year students / Nor Najmah Ahmad ... [et al.] - Ahmad, Nor Najmah; Mat Dangi, Mohamad Ridhuan; Mahmood, Wan Nurashikin; Rahmat Ali, Siti Hafizah (2014)
This exploratory study was carried out to examine several factors that can influence the students in seeking their career once after they finished their studies. This study provides essential information regarding the issue of career seeking among students and to find the determinants that able to influence decision making made by the students for their career choices. This study able to provides an overview about the students' knowledge in their understanding of career prospects. This study uses simple random sampling in selecting the respondents and the targeted population is the final year of social science students. A total of 330 out of 400 questionnaires managed to be returned completely. The respondents for this study are the final year Social Sciences students of UiTM Pahang from various semesters and from a different Diploma programmes. The results from this study shows that personal factors, such as personal values and aspirations, personal career ambition, and the intellectual ability can influence the graduates in the selection of career. Meanwhile for the family and relations factors, the findings revealed that the lecturers in university are significantly impact their influences in the career choice, followed by the relatives or friends that is in the same field and parental wishes can influence the graduates for their career decision making. As for the role played by the university, it shows that student seminar or assignment followed by interesting lectures able to influence graduates in their future career plan. While the occupational factor indicates that, the passion to have a stable and secure future influences their career decision making in the future.